HUBUNGAN PENYULUHAN CUCI TANGAN DENGAN PERILAKU CUCI TANGAN PAKAI SABUN PADA SISWA KELAS 1 DI SD NEGERICENTONG DESA CENTONG KECAMATAN GONDANG KABUPATEN MOJOKERTO - Ma?rifah, Asirotul; Krisdian, Andri (JURNAL KEPERAWATAN SEHAT, 2015)
In a hand with daily activities often contaminated with microbes, so the hand is able to mediate the entry of microbes into the body. One way that the simplest and most commonly done to maintain the cleanliness of hands is by washing hands with soap. Handwashing with soap is practiced correctly and the easiest and effective way to prevent outbreaks of diseases, such as diarrhea, cholera, respiratory infections, intestinal worms, influenza, hepatitis A, and even bird flu. Washing hands with soap and water can be more effectively remove dirt and dust mechanically from the surface of the skin and significantly reduce the number of disease-causing microorganisms such as viruses, bacteria and other parasites on both hands. To know the Conection of Counseling Handwashing with video method With Hand washing Behavior In Grade 1 in elementary school CentongGondang District of Mojokerto. the entire population of students of grade 1 in elementary school CentongGondang District of Mojokertosebanya 36 children with total sampling. Data taken with the observation sheet handwashing using a check list and do a five-step counseling proper hand washing. After the data collected performed data processing and continued with the McNemar test with SPSS Statistics 16.0. the results showed p (0.000) <α (0:05), so that Ho refused meaning there conection extension handwashing with handwashing with soap. To increase hand washing behavior in children, the need for the approach through health education about handwashing with soap is right to change handwashing behavior for the child so that hand washing can be improved.Keywords: hygiene, school-age children, handwashing with soap.